Cryptococcal meningitis patients associated with HIV co-infection admitted in tertiary care hospital–A Case Series - Yadav, Pushpa; Reeta Maurya; Alok Kumar Singh; Sunita Yadav; Gargi Tignath Shukla; Sen, Manodeep (Asian Journal of Medical Sciences, 2024)
Meningitis is a significant infection of the central nervous system that is followed by inflammation of the meninges, resulting in catastrophic neurologic consequences. The inflammation may be caused by infection with viruses, bacteria, fungi, or other microorganisms and less commonly by certain drugs. Meningitis can be life-threatening because of the inflammation’s proximity to the brain and spinal cord; therefore, the condition is classified as a medical emergency. In the present case series, we encompass patient demographics, initial clinical symptoms, physical examinations, laboratory results, cerebrospinal fluid examination findings, treatment side effects, the occurrence of complications, and hospital outcomes. Furthermore, documented were any instances of recurrent cryptococcal meningitis (CM) during follow-up, along with the potential causes of recurrence, the treatment modalities administered, any complications that arose, and the ultimate outcomes. This series reveals CM can manifest alongside HIV co-infection in male patients. Therefore, it is essential to consider the possibility of CM when an immune-compromised patient presents with symptoms such as headaches and other indications of central nervous system involvement. These cases reveal cryptococcosis with HIV-infected patients for rapid and early diagnosis and appropriate treatment of opportunistic infections.